'Land of Fires': Urban Growth, Economic Crisis, and Forest Fires in Attica, Greece. (6th November 2014) - SALVATI, LUCA; RANALLI, FLAVIA
Abstract This study investigates the spatial distribution and basic characteristics of 2692 forest fires between 2000 and 2011 in Attica, Greece, a rapidly expanding urban region. Fire variables were assessed, together with variables describing the socio‐economic local context in three distinct periods of Athens' expansion (2000–2003: semi‐compact expansion and economic growth before the 2004 Olympic Games; 2004–2007: infrastructure development and discontinuous expansion following the Olympic Games; 2008–2011: crisis‐driven decline of the construction industry). Fire characteristics changed over the three periods following the negative trends in the construction industry. Burnt areas decreased in the rural area around Athens and the opposite pattern was observed in the peri‐urban belt. Our findings suggest that the temporal and spatial distribution of forest fires in Attica reflects the construction boom stimulated by the 2004 Olympic Games and the subsequent economic crisis.